(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: Diabetes mellitus is a metabolic disorder which leads to complications that affect the heart, kidney, liver and other vital organs. Most reports on diabetes have focused on diabetes induction using male rat models in short term studies. Objective: Here, we described the induction of diabetes in female rat and the complications of diabetes following long term hyperglycemia in female Wistar rats. Method: Rats were assigned into two groups: control (n=10) and diabetic (n=10). The latter was administered a single (50mg/Kg body weight) intraperitoneal injection of streptozotocin. Bodyweight and blood glucose were assessed for 14 weeks, after which the animals were sacrificed and biochemical and morphology parameters of the liver, kidney and heart were determined. Results: Diabetic rats showed continuous emaciation post STZ induction. The glycated haemoglobin, protein level, lipid profile, liver and kidney function markers were significantly different (p<0.05) from the control. Catalase, superoxide dismutase and glutathione-s-transferase activities were also significantly reduced in the heart, liver and kidney, and a concomitant increase in malondialdehyde concentration was observed. Focal tubular necrosis, pulmonary congestion and mild hyperplasia of kupffer cells were observed in the tissues and all tissues showed negative CD79a expression. Conclusion: This study provides data that could be useful for modelling long-term diabetes mellitus studies in female experimental rat models.